The specific golf swing patterns using K-means clustering with the two-sided confidence interval - Tangwongcharoen, Wisan; Titiroongruang, Wisut (My University, 2017)
Golf is a popular sport for exercise or socializing. It affects an increasing number of patients. Because of these reasons the researchers decided to focus on this problem. We presented the analysis golf swing using K-Means Clustering with Two-Sided Confidence Intervals and the Closest Pair of Points Problem. The raw data were clustered by K-Means Clustering. The boundaries of subgroups processed by K-Means Clustering were calculated to represent the data of the normal and abnormal golfers, which we use as the diagnose patterns. The compared data is the comparison of the diagnose patterns of both normal and abnormal patterns. From the experimental results, the percentage of similar pattern is shown. Therefore, this algorithm can help the doctor to predict the injuries trend of golf players.
Keywords: Closest Pair of Points Problem; K-Means Clustering; Specific Golf Swing Patterns; Two-Sided Confidence Interval